The Effect of Workload on Employee Loyalty with Job Stress as a Moderating Variable at the Department of Manpower, Cooperatives, and Small and Medium Enterprises of Serdang Bedagai Regency - Muhammad Rizky Sembiring; Husni Muharram Ritonga; Elfitra Desy Surya (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study examines the effect of workload on employee loyalty, with job stress as a moderating variable, at the Department of Manpower, Cooperatives, Small and Medium Enterprises of Serdang Bedagai Regency, Indonesia. A quantitative research design was employed using primary data collected from 35 civil servants through structured questionnaires using a Likert scale. Data were analysed using Structural Equation Modeling Partial Least Squares with Smart PLS version 3.0. The measurement model was evaluated through convergent validity, discriminant validity, composite reliability, and Average Variance Extracted, all of which met the recommended threshold values. The structural model demonstrated strong explanatory power, with an R square value of 0.852 for employee loyalty. The findings indicate that workload has a positive and significant effect on employee loyalty. Job stress also shows a significant direct effect on employee loyalty; however, it does not function as a moderating variable in the relationship between workload and employee loyalty. This indicates that job stress neither strengthens nor weakens the effect of workload on loyalty. The study concludes that employee loyalty in public sector institutions is influenced more by structural and normative factors such as job security and organizational commitment rather than psychological conditions alone. Therefore, public organizations are encouraged to implement proportional workload management and comprehensive human resource policies to enhance sustainable employee loyalty.